THE RELATIONSHIP OF DIET WITH THE EVENT OF HYPERTENSION IN THE ELDERLY AT POSYANDU ELDERLY, KEPANJEN DISTRICT - May Utami Incorina Andita Putri; Qori Fanani (Indonesian Journal of Health Care Management, 2022)
Hypertension or high pressure is a very big and serious problem. Hypertension is a health disorder where this condition can not be cured but can be controlled with a healthy lifestyle. Some risk factors to have a role in the occurrence of hypertension were dietary. This research aimed to determine the correlation of diet with hypertension in the elderly at integrated service post elderly Kepanjen in the district of Malang. Nonexperimental research was used in this research with a cross-sectional approach with 85 respondents were selected in this study randomly. Data collection is done by filling out the questionnaire. Furthermore, the data that has been collected using a computer-assisted program by using Correlation Spearman Rho test with a significance level (α) 0,05. A majority 76 (89.4%) in the category of diet that good enough, whereas in degrees of hypertension elderly most 47 (55%) in the category of hypertension stageI. Spearman rank statistical test results showed no relationship between a diet with the incidence of hypertension in the elderly with p> 0,005 and correlation coefficient 0,209. Based on this research people with hypertension disease are expected to always control blood pressure and maintain the diet, such as limiting sodium consumption, fatty foods, and many high fiber foods.